Breastfeeding vs. breast milk transmission during COVID-19 pandemic, which is more important? - He, Yan-fei; Liu, Jun-qiang; Hu, Xiao-dong; Li, Hu-ming; Wu, Ni; Wang, Jie; Jiang, Zhi-gang (Frontiers in Pediatrics, 2023)
The catastrophic coronavirus disease 2019 (COVID-19) pandemic has raised many health questions, and whether breast milk from SARS-CoV-2 infected mothers may be a vector for SARS-CoV-2 transmission has become a hot topic of concern worldwide. Currently, there are extremely limited and conflicting data on the risk of infection in infants through breastfeeding. For this reason, we investigated almost all current clinical studies and systematically analyzed the presence of SARS-CoV-2 and antibodies in the breast milk of mothers infected with SARS-CoV-2, their effects on newborns, and the mechanisms involved. A total of 82 studies were included in this review, of which 66 examined the presence of SARS-CoV-2 in breast milk samples from mothers diagnosed with COVID-19, 29 reported results of antibody detection of SARS-CoV-2 in breast milk, and 13 reported both nucleic acid and antibody test results. Seventeen studies indicated the presence of detectable SARS-CoV-2 nucleic acid in breast milk samples, and only two studies monitored viral activity, both of which reported that infectious viruses could not be cultured from RNA-positive breast milk samples. All 29 studies indicated the presence of at least one of the three antibodies, IgA, IgG and IgM, in breast milk. Five studies indicated the presence of at least one antibody in the serum of breastfed newborns. No COVID-19-related deaths were reported in all 1,346 newborns. Our study suggests that direct breastfeeding does not pose an additional risk of infection to newborns and that breast milk is a beneficial source of anti-SARS-CoV-2 antibodies that provide passive immune protection to infants. In addition, direct breastfeeding would provide maternal benefits. Our review supports the recommendation to encourage direct breastfeeding under appropriate infection control guidelines.